KAJI EKSPERIMENTAL PERFORMANSI PENGEREMAN KAMPAS REM SERAT BONGGOL JAGUNG SEBAGAI BAHAN ALTERNATIF KAMPAS REM MOBIL - Wicaksono, Ryan Bagas (Jurnal Nosel, 2016)
The aims of this research were: (1) To examine the effects of variated composition of corncob powder, brass powder (Cu-Zn), magnesium oxide (MgO), and polyester resin composites on the friction coefficient value in brake pads braking performance test by using Prony brake engine; (2) To investigate which brake pads compositions of corncob powder, brass powder (Cu-Zn), magnesium oxide (MgO), and polyester resin composites that has the highest friction coefficient value; (3) To compare the braking performance of corncob powder brake pads with Nissin brake pads. This research used descriptive and quantitative method. The sampling process was done by making three variations of brake pads compositions. Data were obtained by braking performance test using Prony brake engine then calculated using Prony brake formula. The calculation results were presented in tables and graphs, and then analyzed. The conclusions based on this research were: (1) The variated material compositions of brake pads gave effects on the friction coefficient value of the brake pads. This was indicated by the difference values of friction coefficient values for each brake pads compositions. The friction coefficient value of brake pads composition I which consisted of 20% corncob powder, 40% brass powder, 20% MgO, and 20% polyester resin was 0.342. The friction coefficient value of brake pads composition II which consisted of 30% corncob powder, 30% brass powder, 20% MgO, and 20% polyester resin was 0.395. The friction coefficient value of brake pads composition III which consisted of 40% corncob powder, 20% brass powder, 20% MgO, and 20% polyester resin was 0.354; (2) The most optimal brake pads composition which had the highest friction coefficient value was composition II 0.395 with a composition of 30% corncob powder, 30% brass powder, 20% MgO, and 20% polyester resin; (3) The brake pads with corncob powder material had a good braking performance. The friction coefficient values of all brake pads with corncob powder compositions were higher than Nissin brake pads.